Australian general practitioners initiate statin therapy primarily on the basis of lipid levels; New Zealand general practitioners use absolute risk. Issue 12 (December 2017) - Schilling, Chris; Knight, Josh; Mortimer, Duncan; Petrie, Dennis; Clarke, Philip; Chalmers, John; Kerr, Andrew; Jackson, Rod
Highlights: The basis for initiating statins varies greatly between Australia and New Zealand. New Zealand follows 'best practice' absolute risk-based guidelines. In Australia, statin prescribing is varied and not based on absolute risk. Australia and other countries should adopt clear, uniform guidelines. The New Zealand example shows that 'best practice' prescribing is readily achievable. Abstract: Objectives: To compare the determinants of initial statin prescribing between New Zealand and Australia. New Zealand has a system-wide absolute risk-based approach to primary care cardiovascular disease (CVD) management, while Australia has multiple guidelines. Method: Classification and Regression Tree (CART) analysis of two observational studies of primary care CVD management from New Zealand (PREDICT-CVD) and Australia (AusHeart). Over 80% of eligible New Zealanders have been screened for CVD risk. PREDICT-CVD is used by approximately one-third of New Zealand GPs to perform web-based CVD risk assessment in routine practice, with the sample consisting of 126, 519 individuals risk assessed between 1 January 2007 and 30 June 2014. AusHeart is a cluster-stratified survey of primary care CVD management that enrolled 534 GPs from across Australia, who in turn recruited 1381 patients between 1 April and 30 June 2008. Eligibility was restricted to 55–74 year old patients without prior CVD. Results: The CART analyses demonstrated that New Zealand GPs prescribe statins primarily on the basis of absolute risk, while their Australian counterparts are influenced by a variety of individual risk factors, including total cholesterol, LDL cholesterol and diabetes. Conclusions: Countries seeking to improve their management of CVD should consider adopting a 'whole of system' absolute risk-based approach with clear guidelines that are consistent with drug reimbursement rules; and include computerized decision-support tools that aid decision-making and allow monitoring of outcomes and continual improvement of practice.